2020
DOI: 10.22146/kawistara.34627
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Livelihood Diversification: Tourism Entrepreneurship in a Remote Area of North Halmahera, Indonesia

Abstract: This article aims to describe the capability of public access to social capital as a form of livelihood diversification through tourism entrepreneurship. This idea was originated from the optimization of the tourism sector and the creative economy by the local government since 2017, aiming to encourage creative entrepreneurship in tourism, creative multimedia, and coffee shop businesses. This study was conducted in a qualitative approach; thus, primary and secondary data sources were used to analyze the data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Strategies to maintain business continuity in the face of challenges and threats caused by the Covid-19 pandemic need to be analyzed based on the perspective of capital, the context of vulnerability, and policy and institutional interventions. Previous studies have shown that the use of capital in the dynamics of entrepreneurship depends on the mobility of access to the capital (Singgalen, Kusumawicitra, et al, 2021), policy and institutional interventions to increase the capability of access to the capital (Singgalen, 2020a(Singgalen, , 2020b, to the context of vulnerability (Singgalen, 2021). In addition, shows that human capital is essential in optimizing small-scale business management.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to maintain business continuity in the face of challenges and threats caused by the Covid-19 pandemic need to be analyzed based on the perspective of capital, the context of vulnerability, and policy and institutional interventions. Previous studies have shown that the use of capital in the dynamics of entrepreneurship depends on the mobility of access to the capital (Singgalen, Kusumawicitra, et al, 2021), policy and institutional interventions to increase the capability of access to the capital (Singgalen, 2020a(Singgalen, , 2020b, to the context of vulnerability (Singgalen, 2021). In addition, shows that human capital is essential in optimizing small-scale business management.…”
Section: Introductionmentioning
confidence: 99%
“…The livelihood context of coastal communities will show differences in coping and survival strategies because they are dominated by local culture's structure and values (Singgalen & Simange, 2018). The coping and survival strategy has led to diversification, intensification, extensification, and transformation of livelihood Singgalen et al, 2019aSinggalen et al, , 2019bSinggalen et al, , 2019d.…”
Section: Introductionmentioning
confidence: 99%